Thermal Analysis of Nigerian Oil Palm Biomass with Sachet-Water Plastic Wastes for Sustainable Production of Biofuel - Salman, Bello; Ong, Mei Yin; Nomanbhay, Saifuddin; Salema, Arshad Adam; Sankaran, Revathy; Show, Pau Loke (MDPI, 2019)
Nigeria, being the world's largest importer of diesel-powered gen-sets, is expected to invest in bio-fuels in the future. Hence, it is important to examine the thermal properties and synergy of wastes for potential downstream resource utilization. In this study, thermal conversion as a route to reduce the exploding volume of wastes from sachet-water plastic (SWP) and oil palm empty fruit bunch (OPEFB) biomass was studied. Thermogravimetric (TGA) and subsequent differential scanning calorimeter (DSC) was used for the analysis. The effect of heating rate at 20 °C min-1 causes the increase of activation energy of the decomposition in the first-stage across all the blends (0.96 and 16.29 kJ mol-1). A similar phenomenon was seen when the heating rate was increased from 10 to 20 °C min-1 in the second-stage of decomposition. Overall, based on this study on the synergistic effects during the process, it can be deduced that co-pyrolysis can be an effective waste for energy platform. © 2019 by the authors.